1978
DOI: 10.1042/cs0540193
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Oestrogen and a Progestogen on Bone Loss in Postmenopausal Women

Abstract: 1. The value of progestogen therapy in the prevention of postmenopausal bone loss was assessed in 30 women, by a preliminary randomized controlled trial of gestronol or mestranol, in comparison with a placebo. 2. When the skeletal response was measured by photon absorptiometry, bone mineral loss was prevented by both the oestrogen and the progestogen. 3. We confirm that mestranol significantly reduced the urinary output of hydroxyproline-containing peptide, but this did not occur during gestronol therapy, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…4). The finding that progesterone (at a much higher concentration than E2), increased CK specific activity in cultured bone-derived cells requires further study, since progesterone has been reported to have a beneficial effect on bone loss in postmenopausal osteoporosis (25). In male diaphyseal bone, in contrast to female bone, T but not E2 stimulated CK specific activity.…”
Section: Discussionmentioning
confidence: 99%
“…4). The finding that progesterone (at a much higher concentration than E2), increased CK specific activity in cultured bone-derived cells requires further study, since progesterone has been reported to have a beneficial effect on bone loss in postmenopausal osteoporosis (25). In male diaphyseal bone, in contrast to female bone, T but not E2 stimulated CK specific activity.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that 0.625 mg of conjugated estrogen (CE) is adequate to maintain bone mass in a postmenopausal woman [26,31], but 0.3 mg may suffice when given in conjunction with calcium supplementation [32]. In some studies, the addition of progestin provided additional benefit [33,34].…”
Section: Estrogen Replacement Therapy Estrogen and Osteoporosismentioning
confidence: 99%
“…There is evidence that progestogens have a protective effect against demineralisation of bone [15] and relieve hot flushes [16]. Although results of past studies with progestogens have shown variable effects on fibroids, degenerative changes with high dose therapy have been reported [17], suggesting a possible role for combination with LHRH analogues.…”
Section: Lhrh Analogues In Combination With Progestogensmentioning
confidence: 99%